2022
DOI: 10.1002/sia.7174
|View full text |Cite
|
Sign up to set email alerts
|

Efficient electrochemical reduction of nitrogen from biomass doped boron and nitrogen under ambient conditions

Abstract: The discovery of extremely effective heteroatom dopant catalysts for electrochemical reduction reactions is crucial for ambient nitrogen fixation. In this paper, we investigated nitrogen and boron doped biomass carbon as an effective electrocatalyst for nitrogen reduction reaction (NRR), where the N, B content ratio, and pyrolysis temperature were optimized to improve N2 adsorption and N≡N cleavage. The resulting 600ACNB‐213 exhibits outstanding improvement in fixing N2 to ammonia with a high ammonia productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Apart from that, the intrinsic semiconducting nature of main group elements shows sluggish electronic conductivity which further restricts HER process as it is highly dependent on surface electrons availability [109]. In this regard, Chen et al [110] demonstrated that boron doping onto the basal Boron and nitrogen were co-doped into biomass carbon leading to the generation of pyridinic-N and BC 2 O acting as active site for NRR as investigated by Tian et al [111] with the ammonia production rate of 41 µg h −1 mg −1 cat at −1 V vs RHE. XPS analysis data showed gradual shifting in the binding energy of boron and nitrogen depicting about synergism occurring between boron and nitrogen centers producing sufficient charge density for NRR process.…”
Section: D-block and P-block Heteroatom Dopingmentioning
confidence: 99%
“…Apart from that, the intrinsic semiconducting nature of main group elements shows sluggish electronic conductivity which further restricts HER process as it is highly dependent on surface electrons availability [109]. In this regard, Chen et al [110] demonstrated that boron doping onto the basal Boron and nitrogen were co-doped into biomass carbon leading to the generation of pyridinic-N and BC 2 O acting as active site for NRR as investigated by Tian et al [111] with the ammonia production rate of 41 µg h −1 mg −1 cat at −1 V vs RHE. XPS analysis data showed gradual shifting in the binding energy of boron and nitrogen depicting about synergism occurring between boron and nitrogen centers producing sufficient charge density for NRR process.…”
Section: D-block and P-block Heteroatom Dopingmentioning
confidence: 99%
“…[141] Tian et al studied N and B co-doped biomass-derived carbons as electrocatalysts for NRR, they found that pyridine-N and BC 2 O are active centers for synthesizing ammonia, these positions can significantly improve the overall catalytic performance, they optimized the N/B content ratio and pyrolysis temperature to improve N 2 adsorption and N�N cracking. [147] Li et al reported a biomass-derived N doped porous carbon (named NC-800) electrocatalyst for NRR. NC-800, which contain approximately 8 wt % of N elements, was obtained from bamboo shoots.…”
Section: Co 2 Rrmentioning
confidence: 99%
“…Tian et al. studied N and B co‐doped biomass‐derived carbons as electrocatalysts for NRR, they found that pyridine‐N and BC 2 O are active centers for synthesizing ammonia, these positions can significantly improve the overall catalytic performance, they optimized the N/B content ratio and pyrolysis temperature to improve N 2 adsorption and N≡N cracking [147] . Li et al.…”
Section: Electrocatalysts Based On Biomass Derived Porous Carbonmentioning
confidence: 99%